2011
DOI: 10.1002/pola.24713
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amphiphilic ABC triblock copolymers by single electron transfer nitroxide radical coupling reaction in tetrahydrofuran

Abstract: A series of ABC triblock copolymers, that is, polyisoprene‐block‐polystyrene‐block‐poly(ethylene oxide) (PI‐PS‐PEO), PI‐block‐poly(tert‐butyl acrylate)‐block‐PEO (PI‐PtBA‐PEO), and PI‐block‐poly(acrylic acide)‐block‐PEO (PI‐PAA‐PEO) were obtained by combination of anionic technique, atom transfer radical polymerization (ATRP), and single electron transfer nitroxide coupling (SETNRC) reaction. Anionic polymerization of isoprene followed by end capping with ethylene oxide yielded hydroxyl‐terminated PI. After es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…The most well‐known CLRP techniques are transition metal mediated polymerization (e.g., atom transfer radical polymerization (ATRP)12, 13 and Cu(0)‐mediated radical polymerization (single electron transfer‐living radical polymerization, SET‐LRP)14, 15), reversible addition fragmentation chain transfer (RAFT)16–18 polymerization, and nitroxide‐mediated radical polymerization (NMP) 3, 11, 19. CLRP techniques are often used in conjunction with “click” chemistry methods for synthesis of structurally advanced macromolecules 20–28. However, to achieve high yield and satisfactory reproducibility by such a tandem approach, it is crucial that high end‐group fidelity (“livingness”) is maintained during the CLRP step 29, 30.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well‐known CLRP techniques are transition metal mediated polymerization (e.g., atom transfer radical polymerization (ATRP)12, 13 and Cu(0)‐mediated radical polymerization (single electron transfer‐living radical polymerization, SET‐LRP)14, 15), reversible addition fragmentation chain transfer (RAFT)16–18 polymerization, and nitroxide‐mediated radical polymerization (NMP) 3, 11, 19. CLRP techniques are often used in conjunction with “click” chemistry methods for synthesis of structurally advanced macromolecules 20–28. However, to achieve high yield and satisfactory reproducibility by such a tandem approach, it is crucial that high end‐group fidelity (“livingness”) is maintained during the CLRP step 29, 30.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Percec, Haddleton, and co‐workers have demonstrated that Cu(0)‐mediated radical polymerization (SET‐LRP) displays near perfect bromide end‐group fidelity until relatively high conversion (typically 80%) for various monomers in polar solvents,14, 36–44 thus allowing precise synthesis of complex polymer architectures 24, 45–55. The AGET/ATRP technique in apolar solvents, developed by Matyjaszewski and coworkers,56, 57 enables significant reduction in the amount of metal catalyst used as well as marked improvement in end‐group fidelity (relative to direct ATRP; typically ∼87% end‐group fidelity at 90% monomer conversion) 31, 56, 57.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the challenges, herein, we present a mild and efficient strategy for the covalently functionalization of GO sheets via surface initiated single‐electron‐transfer living radical polymerization (SET‐LRP) 41–46. SET‐LRP is a highly efficient methodology allowing for the ultrafast synthesis of linear and more complex topology under mild conditions 47–54. In SET‐LRP, the balance between dormant and active chains is mediated by an outer‐sphere heterolytic SET activation process via Cu 0 surfaces and deactivation with Cu II X 2 / N ‐ligand 55–58.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46] SET-LRP is a highly efficient methodology allowing for the ultrafast synthesis of linear and more complex topology under mild conditions. [47][48][49][50][51][52][53][54] In SET-LRP, the balance between dormant and active chains is mediated by an outer-sphere heterolytic SET activation process via Cu 0 surfaces and deactivation with Cu II X 2 /Nligand. [55][56][57][58] In comparison with other metal-catalyzed LRP processes, SET-LRP shows significantly rapid rate of polymerization at room temperature or below, [59][60][61][62][63] which brings us a new opportunity to efficiently grow polymeric chains from the surface of GO without destroying the oxygen-containing functional groups.…”
mentioning
confidence: 99%
“…49 It is considered to be an inner sphere electron‐transfer mechanism in which a low oxidation state metal complex acts as the catalyst, mediating a fast exchange between radicals and their dormant alkyl halide species. As compared with classic ATRP, SET‐LRP should be an alternative controlled LRP, which can be occurred at room temperature, atmosphere and aqueous solution with rapid polymerization rate . Given these advantages, SET‐LRP has rapidly attracted great research attention and explored for various applications including the surface modification of carbon nanomaterials …”
Section: Introductionmentioning
confidence: 99%